PERPADUAN BUDAYA MELAYU DAN NILAI-NILAI ISLAM DALAM KEHIDUPAN MASYARAKAT DI LINGKUNGAN ISTANA MAIMU - Ika Purnamasari; Fariza Nikalya; Indri Putri Yani; Keysyah Usri Safira; Loinel Hutapea; Elsa Rolutio (STKIP Subang, 2026)
This study aims to analyze the integration of Malay culture and Islamic values in the daily life of the community around Maimun Palace in Medan. This research uses a qualitative approach to understand social and cultural phenomena in depth. Data were collected through semi-structured interviews with local communities, traditional leaders, and individuals who understand Malay traditions, as well as literature studies from journals and related sources. The results show that Malay culture and Islamic values are closely intertwined and mutually reinforcing in various aspects of life, including communication ethics, social interactions, dress codes, and traditional practices. The principle of “adat bersendikan syarak, syarak bersendikan Kitabullah” is reflected in the community’s daily behavior and social norms. Furthermore, traditional ceremonies such as marriage, birth, and death rituals demonstrate that customs do not contradict Islamic teachings but instead strengthen religious values. Despite the challenges of modernization, the community continues to preserve these values as part of their cultural identity. Therefore, the environment of Maimun Palace represents a living cultural space where the integration of tradition and religion is maintained sustainably.